A psychrophilic caseinolytic aspartic protease from the freshwater amphipod Gammarus bakhteyaricus for application in milk coagulation. (January 2022) - Azadi, Mohammad Ali; Hemmati, Roohullah; Homaei, Ahmad; Khalaji-Pirbalouty, Valiallah
Abstract: In the present study, a novel aspartic protease was purified from Gammarus bakhteyaricus (25 kDa). The optimum temperature and pH values were found to be 20 °C and 6 respectively. Besides, the values of Km and V m a x for casein, as substrate, are reported to be 5 nM and 5.6 μmole min − 1 respectively. The calculated value of kcat was 778 s − 1 while the catalytic efficiency was obtained as 154, 321 μmol L −1 s −1 Moreover, Δ H D #, Δ G D #, and Δ S D # values were calculated to be 8.676 kcal mol − 1, 122.364 kcal mol − 1, and 0.047 kcal mol − 1 K − 1, respectively. In addition to casein, it was found that the new enzyme degrades different proteins and is inhibited by pepstatin A. Furthermore, the enzyme retained most of its activity in the presence of KCl, NaCl and CaCl2 up to 40 mmol/L. The results indicate that the novel aspartic protease could be used in dairy processing such as milk coagulation at low temperatures. Highlights: A novel psychrophilic aspartic protease was purified from Gammarus bakhteyaricus. The optimum temperature and pH of the enzyme were 20 °C and 6 respectively. The novel enzyme hydrolyzes casein and milk skim, efficiently. The inhibitory effects of metal ions on the enzyme activity were insignificant. The novel aspartic protease can be used in dairy industry for milk clotting.